PENGARUH HUMAN RELATION, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. PRATAMA AGRO SAWIT (PAS) DI BATIN XXIV KABUPATEN BATANG - Etty Siswati; Evi Fauzani (Universitas Batanghari Jambi, 2018)
The aim of this study. To find out the effect of human relations, motivation and work environment on employee performance at PT. Pratama Agro Sawit (PAS) in Batin XXIV Kabupeten Batanghari. The method of collecting data is used survey method used to obtain information from respondents by using interview techniques and distributing questionnaires and using Likert scale measurements. the sample in this study were employees at PT. Pratama Agro Sawit (PAS) in Batin XXIV Kabupaten Batanghari. The analytical tool used is a multiple linear regression method using computer assistance through the SPSS 20.0 for Windows program. From the calculation of SPSS 20.0 obtained variable human relations tcount of 3.517, due to tcount> from t table, (3.517> 1.66571, meaning that the independent variable has an influence on the dependent variable, which means there is a partial influence between human relations variables on employee performance at PT . Pratama Agro Sawit in Batin XXIV Kabupaten Batanghari . Motivation variables are 6.515, due to t count> from t table, (6.515> 1.66571), meaning that the independent variable has an influence on the dependent variable, which means there is a partial influence between motivation and achievement employee work at PT. Pratama Agro Sawit (PAS) in Batin XXIV Kabupaten Batanghari. Variable work environment is 0.971. Due to t count <from t table, (0.971 <1.66571) means that the independent variable has no influence on the dependent variable, which means there is no influence partial between work environment and work performance ryawan at PT. Pratama Agro Sawit (PAS) in Batin XXIV Kabupaten Batanghari. Simultaneous test (F Test), it can be concluded that the variable human relations, motivation and work environment shows a significant influence on employee performance at PT. Pratama Agro Sawit (PAS) in Batin XXIV, which is proven by the value of F count 35,821 of greater than F table df n - k-1 then 78 - 3- 1 = 74 (F table = 2.73 or (35,821 > 2,73) The summary model of PT Pratama Agro Sawit (PAS) in Batin XXIV above can be seen that the Adjusted R Square value is 0.668, so it can be concluded that the percentage influences human relations (X1), motivation (X2), and work environment variables (X3 ) the variable employee performance at PT Pratama Agro Sawit (PAS) is 0.668 or 66.8% and the remaining 0.332 or 33.2% is influenced by other variables not examined in this study.